NUTRITION AND ORAL HEALTH IN CHILDREN - Ancuta Lupu; Gabriela Paduraru; Felicia Dragan; Magdalena Starcea; Vasile Valeriu Lupu; Stefana Moisa; Ileana Ioniuc; Pertea Leonard Iosif; Vasile Eduard Rosu; Ingrith Miron (Romanian Society of Oral Rehabilitation, 2019)
Oral health is integrated into general health and it is essential to well-being and quality of life. Oral and systemic health is conditioned by proper nutrition. This article highlights the consequences of inadequate nutrition on oral health in children and how certain vitamin or nutrient deficiencies can condition the occurrence of different diseases at this level. Diseases of the oral cavity can be prevented both by proper and balanced nutrition, and by proper hygiene. Nutritional habits and, implicitly, oral and systemic health should be taken into account, as children's oral health is a predictor for the oral health of the future adults.